PENGARUH TINGKAT PEMAHAMAN AKUNTANSI DAN TINGKAT KESIAPAN PELAKU UMKM PASAR SEGAR KOTA MAKASSAR TERHADAP PENERAPAN SAK EMKM - Parmawati, Risma; Fadillah, Andi Lutfyatul; Putri, Ila Fadila; Muchran, Muchriana (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2024)
The aim of this research is to determine the level of accounting understanding of Makassar City Fresh Market MSME actors regarding the implementation of SAK EMKM. This research uses a quantitative type of research, uses a descriptive approach and uses multiple linear regression analysis tests. This data was obtained by distributing questionnaires directly to MSME players at Pasar Segar Makassar. Quantitative research was chosen because it aims to test the hypotheses that have been proposed. Research on certain populations or samples can be carried out using a descriptive approach, which comes from positivism. For analysis, T, F, and R Square tests were used. The research sample was MSME actors in the Fresh Market, Makasaar City. The results of this research show that the accounting understanding variable (X1) does not have a significant influence on the application of SAK EMKM (Y), but the variable level of readiness of MSME actors (X2) has a significant influence on the application of SAK EMKM (Y). The variables level of understanding of accounting (X1) and level of readiness of MSME actors (X2) each have an influence of 29.9% on the variable implementing SAK EMKM (Y).